Sustainability of chicken meat production in achieving food security in Malaysia - Samsuddin, Nur Syahirah; Sharaai, Amir Hamzah; Ismail, Mohd Mansor (American-Eurasian Network for Scientific Information, 2015)
Background:Chicken meat is vital in Malaysia since protein-based food is needed in human’s diet and the meat is socially and religiously acceptable by Malaysian. Hence, in order to ensure sufficient supply of chicken meat at affordable price either for present or future consumption, sustainable chicken meat production is needed. Objectives: The aim of this paper is to discuss the framework of sustainable chicken production in ensuring food security. Results: Chicken production industries in Malaysia had rapidly increase due to the increase in demand for consumption. Demand of halal food and increase in cost of living is a main issue of food security in Malaysia Conclusion: Thus, the sustainable production framework in poultry production had been importance in combating the food security issues in Malaysia.